Transforming payment processing through lean and kaizen management : A Malaysian public service perspective (Global Business Management Review (GBMR), 2025)
Lean management has emerged as a transformative methodology for optimizing operational efficiency and reducing waste in various sectors. However, its application within public office environments, particularly in payment processing services, remains underexplored. This study investigates the implementation of Lean and Kaizen methodologies in a Malaysian Government-Linked Company (GLC) responsible for payment processing. Lean management focuses on eliminating waste and optimizing processes, while Kaizen is a continuous improvement strategy that enhances operational efficiency through incremental changes. The study highlights significant inefficiencies in service delivery, with Service Level Agreement (SLA) performance scores fluctuating between 54.68% and 95.16% from January to July 2020, indicating an urgent need for process optimization.Using Value Stream Mapping (VSM), Kaizen burst events, and structured problem-solving techniques, the study identifies key bottlenecks in file movement, verification, and approval processes. VSM is a Lean tool that visualizes and analyzes workflows to detect inefficiencies and streamline operations. Through targeted Lean interventions, the organization successfully achieved a minimum SLA performance threshold of 82%, demonstrating improved workflow efficiency, reduced lead times, and enhanced employee engagement. The findings emphasize the potential of Lean and Kaizen in optimizing administrative processes in the public sector, advocating for wider adoption and further empirical research in this domain.